2016
DOI: 10.3892/ijo.2016.3709
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic cancer treatment: The great discovery and greater complexity (Review)

Abstract: The discovery of tumor angiogenesis opened a new path in fighting cancer. The approval of different antiangiogenic agents, most targeting vascular endothelial growth factor (VEGF) signaling, has either increased the effectiveness of standard chemotherapy or even replaced it by offering better patient outcomes. However, an increasing number of preclinical and clinical observations have shown that the process of angiogenesis is far from clearly understood. Apart from targeting the VEGF pathway, novel strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
95
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(98 citation statements)
references
References 115 publications
2
95
1
Order By: Relevance
“…The first concept of antiangiogenic therapy aimed to destroy tumour vessels, while it turned out that, paradoxically, antiangiogenic drugs normalised vasculature and as a result offered an improvement in chemotherapeutic delivery [13, 14]. The results of the present study support the positive importance of the normalisation of tumour vasculature rather than destruction.…”
Section: Discussionsupporting
confidence: 71%
“…The first concept of antiangiogenic therapy aimed to destroy tumour vessels, while it turned out that, paradoxically, antiangiogenic drugs normalised vasculature and as a result offered an improvement in chemotherapeutic delivery [13, 14]. The results of the present study support the positive importance of the normalisation of tumour vasculature rather than destruction.…”
Section: Discussionsupporting
confidence: 71%
“…The discovery of tumour angiogenesis opened a new path in fighting cancer that increased the effectiveness of standard chemotherapy, or even replaced it, by offering better patient outcomes [32]. Over the past decade, extensive studies of 3D cultures have demonstrated differences compared to the behaviour of cells on 2D surfaces [33].…”
Section: Discussionmentioning
confidence: 99%
“…It differs from other chemotherapeutic strategies by targeting the tumour vasculature rather than neoplastic cells. However, the response to anti‐angiogenic therapy is variable because angiogenic activity differs among tumour types and at different locations within the same tumour, caused, in part at least, by multiple vascularisation mechanisms being utilised at these different sites …”
Section: Control Of Angiogenesismentioning
confidence: 99%